The stability of punishment: A follow-up of Blumstein's hypothesis - Tremblay, Pierre (Journal of quantitative criminology, 1986)
Because of the intrinsic relativity of social tolerance toward crime, the rate of punishment that a given society inflicts on its criminals is expected to remain relatively constant over the long term, in spite of social changes and increasing or decreasing crime rates. This paper reconstructs the penal behavior of Montreal's criminal justice from 1845 to 1913 and finds that the stability hypothesis, all things considered, works quite well and has much heuristic value. Three problems, somewhat bypassed in the existing literature, are dealt with here: the reliability of penal statistical time series, the direct empirical evidence of stabilization processes, and a rather crude way of measuring prison punishment. It is suggested, furthermore, that the stability hypothesis include in its future argument the impact of increasing policing and that it be confined tentatively to modern western societies.